2013
DOI: 10.1111/j.1751-908x.2012.00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Rare Earth and High Field‐Strength Elements in the Multani Mitti Clay: A Study Using INAA

Abstract: Instrumental neutron activation analysis was used to determine nine rare earth elements (REE), Sc and five high field-strength elements (HFSE) in the Multani Mitti (MM) clay. Chondrite-normalised rare earth element patterns for the MM clay compared with those for the Post-Archaean Australian Shale (PAAS), Upper Continental Crust (UCC) and North American Shale Composite (NASC) showed enrichment of light REEs and depletion of heavy REEs with a slight negative Eu anomaly. The Multani Mitti clay showed close resem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…For example, positive Eu and negative Ce anomalies are often used to indicate the occurrence of hydrothermal activities (Gu et al, 2019; Qi et al, 2021; Su et al, 2022). REEs data shown as Post‐Archaean Australian Shale (PAAS)‐normalized diagrams (Shahida et al, 2013) for different dolomite fabrics are shown in Figure 6. The REEs patterns for the MD samples are characterized by slightly Ce negative anomalies, and slightly Eu positive anomalies (Figure 6a).…”
Section: Resultsmentioning
confidence: 99%
“…For example, positive Eu and negative Ce anomalies are often used to indicate the occurrence of hydrothermal activities (Gu et al, 2019; Qi et al, 2021; Su et al, 2022). REEs data shown as Post‐Archaean Australian Shale (PAAS)‐normalized diagrams (Shahida et al, 2013) for different dolomite fabrics are shown in Figure 6. The REEs patterns for the MD samples are characterized by slightly Ce negative anomalies, and slightly Eu positive anomalies (Figure 6a).…”
Section: Resultsmentioning
confidence: 99%
“…Multani mitti is a clay deposit found in Pakistan, it is found in plenteous deposits, which are located in Multan. Scientifically, Multani mitti is a mineral of montmorillonite smectite and bentonite clay, From the ancient Chinese, Mesopotamians, Egyptian, and Indian civilizations, it is easy to find out various beneficial and curative effects of clay [6]. Clay has a variety of applications i.e.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray uorescence spectrometry (XRF) and instrumental neutron activation analysis (INAA) have been widely used for the determination of Zr-Nb or Hf-Ta, respectively. 5,6 However, these techniques cannot be used to analyse these four elements simultaneously because of their inadequate sensitivity for many geological materials. 1 A highly sensitive and multi-element simultaneous analytical method based on inductively coupled plasma mass spectrometry (ICP-MS) has been developed to measure the contents of HFSEs and other trace elements over the past three decades.…”
Section: Introductionmentioning
confidence: 99%